2020
DOI: 10.3390/nu12061840
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Nutritional Value and Physical Properties of Blenderised Enteral Nutrition Formula: A Systematic Review and Meta-Analysis

Abstract: Background: Although there are merits in using commercial “enteral nutrition formula” (ENF) compared with blended ENF, there is a growing preference for the use of blended ENF in many countries globally. However, the nutritional value and physical properties of blended ENF compared with commercial ENF may be limiting its use. We have not found any evidence of a meta-analysis on the nutritional value of blended diets in the adult population. Aim: The aim of this review was to compare the nutritional value, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
1
22
0
2
Order By: Relevance
“…26 Viera et al 27 showed that BTF provided 50% less energy and macronutrient values than prescribed, and de Sousa et al 14 reported lower energy content than estimated. These findings are supported by others not included in this review, [31][32][33] indicating that this is a major concern. Indications of lower energy content than expected were also seen in the study by Gallagher et al, 18 who showed that an increase of up to 1.5 times in calories was required with BTF compared with CTF to sustain adequate growth.…”
Section: Nutrition In Clinical Practicesupporting
confidence: 87%
“…26 Viera et al 27 showed that BTF provided 50% less energy and macronutrient values than prescribed, and de Sousa et al 14 reported lower energy content than estimated. These findings are supported by others not included in this review, [31][32][33] indicating that this is a major concern. Indications of lower energy content than expected were also seen in the study by Gallagher et al, 18 who showed that an increase of up to 1.5 times in calories was required with BTF compared with CTF to sustain adequate growth.…”
Section: Nutrition In Clinical Practicesupporting
confidence: 87%
“…One potential mechanism concerns how the electrolytes in the enteric nutrition may interact with the endothelial cells in lung tissue. Enteric fluid contains proteins, carbohydrates, fats, vitamins, and minerals including calcium (8). When calcium reaches the lung endothelium, it enters through transient receptor potential channels.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that when the amount of energy and macronutrients required for patients is not provided there is a reduction in the effectiveness of nutrition therapy, which can result in malnutrition, including energy malnutrition, increased morbidity and mortality, hospital readmission, and home care costs. 55 Therefore, there is a clear need to devise strategies and actions to minimize differences in the supply of EN. 56 Examples of such strategies include providing guidance to caregivers and patients regarding a preference for seasonal foods because they contain greater nutrition value, 57 weighing ingredients, and not changing items in prescribed recipes to ensure the standardization of measures provided in the home.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that when the amount of energy and macronutrients required for patients is not provided there is a reduction in the effectiveness of nutrition therapy, which can result in malnutrition, including energy malnutrition, increased morbidity and mortality, hospital readmission, and home care costs 55 . Therefore, there is a clear need to devise strategies and actions to minimize differences in the supply of EN 56 .…”
Section: Discussionmentioning
confidence: 99%